2023
DOI: 10.3390/ijms24119509
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Indigenous Rhizobia from Kenyan Soils Nodulating with Common Beans

Abstract: Kenya is the seventh most prominent producer of common beans globally and the second leading producer in East Africa. However, the annual national productivity is low due to insufficient quantities of vital nutrients and nitrogen in the soils. Rhizobia are symbiotic bacteria that fix nitrogen through their interaction with leguminous plants. Nevertheless, inoculating beans with commercial rhizobia inoculants results in sparse nodulation and low nitrogen supply to the host plants because these strains are poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…In this study, the prediction results of bacterial functions showed dominant roles of nitrogen fixation, cellulolysis and ureolysis in the rhizosphere soil of D. sinicus, indicating a high capacity for carbohydrate conversion and biological nitrogen fixation [11]. Remarkably, the rhizosphere microbes of the straight type possessed higher nitrogen fixing capacity, which could lead to higher soil NH 4 + -N content compared to the introduced straight type (Tables 1 and S3) [48]. Furthermore, the FUNGuild analysis revealed a high proportion of saprotrophic fungi, which enhanced the availability of carbon and nitrogen [49,50].…”
Section: Influence Of Rhizosphere Microbes On Nh 4 + -N Availability ...mentioning
confidence: 64%
See 3 more Smart Citations
“…In this study, the prediction results of bacterial functions showed dominant roles of nitrogen fixation, cellulolysis and ureolysis in the rhizosphere soil of D. sinicus, indicating a high capacity for carbohydrate conversion and biological nitrogen fixation [11]. Remarkably, the rhizosphere microbes of the straight type possessed higher nitrogen fixing capacity, which could lead to higher soil NH 4 + -N content compared to the introduced straight type (Tables 1 and S3) [48]. Furthermore, the FUNGuild analysis revealed a high proportion of saprotrophic fungi, which enhanced the availability of carbon and nitrogen [49,50].…”
Section: Influence Of Rhizosphere Microbes On Nh 4 + -N Availability ...mentioning
confidence: 64%
“…Nitrogen (N) is one of the major elements essential for plant growth [6,48]. Soil N ammoniation and nitrification, as key processes in nitrogen cycling and plant nutrition absorption, are mainly mediated by soil microbes [4,5].…”
Section: Influence Of Rhizosphere Microbes On Nh 4 + -N Availability ...mentioning
confidence: 99%
See 2 more Smart Citations